Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

See my fourier series calculation of this function if you please!

$ f(t)=\left\{\begin{array}{ll} 0, & \text{for } \ -\pi<t<0 \\ 1, & \text{for } \ 0 < t < \pi\end{array}\right. . $

I start by calculation of the coefficient $a_0,a_k,b_k$: $$a_0=\frac{1}{\pi} \int\limits_{0}^{\pi}1\mathrm dt=1 ;$$ $$ a_k=\frac{1}{\pi}\int\limits_{0}^{\pi}\sin(kt)\mathrm dt=\frac{1-\cos(\pi k)}{\pi k} = \frac{1-(-1)^{k}}{\pi k};$$ $$ b_k= \frac{1}{\pi}\int\limits_{0}^{\pi}\cos(kt)\mathrm dt = \frac{\sin(\pi t)}{k} = 0$$

We will get: $f(t) \sim \frac{1}{2} + \sum\limits_{k=0}^{\infty}\frac{1-(-1)^{k}}{\pi k}\sin(kt) = \frac{1}{2} + \sum\limits_{n=0}^{\infty}\frac{2}{\pi (2n+1)}\sin((2n+1)t) $

How we can find relationship : $\sum\limits_{n=0}^{\infty}\frac{(-1)^n}{2n+1}=\frac{\pi}{4}$ from this fourier series ?

share|cite|improve this question
Do you mean $$ f(t)=\left\{\begin{array}{ll} 0, & for \ -\pi<t<0 \\ 1, & for \ 0 < t < \pi\end{array}\right. $$ – Américo Tavares Feb 2 '13 at 14:14
Hi , I just copy from paper, it is like I wrote in beginning... But I also think it is strange because I don't know how to make a fourier series of a function which give two value.... So is very likely it is a mistake in typing. – booth Feb 2 '13 at 14:20
You forgot to divide your coefficients by $\pi$: Also, in $a_k$, the numerator should be $-\cos(\pi k)+\cos (0)=1-(-1)^k$. – 1015 Feb 2 '13 at 14:29
I correct it thank you )) – booth Feb 2 '13 at 14:40
Note also that with the formula you took for $a_0$, it should be $a_0/2$ in the Fourier series of $f$. And your $a_k$ should be called $b_k$ and vice versa. – 1015 Feb 2 '13 at 14:44
up vote 5 down vote accepted

$$\begin{equation*} % a_0 f(t)=\begin{cases}0,&-\pi<t<0\\1,&0<t<\pi \end{cases} \end{equation*}$$

f(t) \begin{equation*}a=-\pi\qquad l=\pi\qquad a+2l=\pi\qquad\qquad\qquad\end{equation*}

$$\begin{equation*}S(t)=\frac{a_0}2+\sum\limits_{k=1}^\infty a_k\cos\left(\frac{k\pi x}l\right)+b_k\sin\left(\frac{k\pi t}l\right)\\ \\ a_0=\frac1l\int\limits_{a}^{a+2l}f(t)\mathrm dt\qquad a_k=\frac1l\int\limits_{a}^{a+2l}f(t)\cos(t)\mathrm dt\qquad b_k=\frac1l\int\limits_{a}^{a+2l}f(t)\sin(t)\mathrm dt\\ \\\end{equation*}$$

\begin{align*} % a_0 a_0&=\frac1\pi\int\limits_{-\pi}^\pi f(t)\,\text dt\\ &=\frac1\pi\int\limits_{0}^\pi\,\text dt\\ &=\frac t\pi \Big|_0^\pi\\ &=\frac{\pi-0}\pi\\ &=1\\ \end{align*}

\begin{align*} %a_k a_k&=\frac1\pi\int\limits_{-\pi}^\pi f(t)\cos(kt)\,\text dt\\ &=\frac1\pi\int\limits_{0}^\pi \cos(kt)\,\text dt\\ &=\frac1\pi\frac{\sin(kt)}k\Big|_0^\pi\\ &=\frac{\sin(k\pi)}{\pi k}\\ &=0 \end{align*}

\begin{align*} % b_k b_k&=\frac1\pi\int\limits_{-\pi}^\pi f(t)\sin(kt)\,\text dt\\ &=\frac1\pi\int\limits_{0}^\pi\sin(kt)\,\text dt\\ &=\frac{-\cos(kt)}{\pi k}\Big|_0^\pi\\ &=\frac{\cos(0)-\cos(k\pi)}{k\pi }\\ &=\frac{1-(-1)^k}{k\pi }\\ &=\frac{1+(-1)^{k+1}}{k\pi }\\ \end{align*}

\begin{align*} % S(t) S(t)&=\frac{1}2+\sum\limits_{k=1}^\infty \frac{1+(-1)^{k+1}}{k\pi }\sin\left({k t}\right)\\ &=\frac{1}2+\frac2\pi\sum\limits_{k=1,3,5,\dots}^\infty\frac{\sin({k t})}k\\ &=\frac{1}2+\frac2\pi\sum\limits_{r=1}^\infty\frac{\sin\big((2r-1)t\big)}{2r-1}\\ \\ &=\frac12+\frac2\pi\left(\sin(t)+\frac{\sin(3t)}3+\frac{\sin(5t)}5+\dots\right) \end{align*}


\begin{align*} % S(t) S(t) &=\frac{1}2+\frac2\pi\sum\limits_{r=1}^\infty\frac{\sin\big((2r-1)t\big)}{2r-1}\\ \\ \\% S(π/2) S\left(\tfrac\pi2\right) &=\frac{1}2+\frac2\pi\sum\limits_{r=1}^\infty\frac{\sin(\pi r-\tfrac\pi2)}{2r-1}\\ 1&=\frac{1}2+\frac2\pi\sum\limits_{r=1}^\infty\frac{(-1)^{r-1}}{2r-1}\\ \frac\pi4&=\sum\limits_{r=1}^\infty\frac{(-1)^{r-1}}{2r-1}\\ \\ \end{align*}

share|cite|improve this answer
You might want to justify the convergence at $\pi/2$. – 1015 Feb 2 '13 at 15:18
waw, thank a lot unklerhaukus ) – booth Feb 2 '13 at 15:49

The Fourier series of $f$ is: $$ \frac{1}{2}+\sum_{k=1}^{+\infty} \frac{1-(-1)^k}{k\pi}\sin(kt)=\frac{1}{2}+\sum_{n=0}^{+\infty}\frac{2}{(2n+1)\pi}\sin((2n+1)t). $$

Now the function $f$ is differentiable at $t=\pi/2$. By Dirichlet Theorem, we have convergence of the Fourier series to $f$ at this point: $$ 1=\frac{1}{2}+\sum_{n=0}^{+\infty}\frac{2}{(2n+1)\pi}\sin((2n+1)\pi/2)=\frac{1}{2}+\sum_{n=0}^{+\infty}\frac{2}{(2n+1)\pi}(-1)^n. $$ This yields the required formula.

share|cite|improve this answer
You have my thank julien!!! – booth Feb 2 '13 at 15:48
@booth You're welcome. Since you chose to accept the other answer, note nevertheless that it is important in such an exercise to justify the convegence of the Fourier series to $f$ at $\pi/2$. This is not automatic. – 1015 Feb 2 '13 at 15:50

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.